REGRESSION ANALYSIS: RELATIONSHIP BETWEEN COVID-19 VACCINATION AND POSITIVITY RATE IN INDONESIA - Fida Fathiyah Addini (LPPM Universitas Bina Bangsa, 2023)
Covid-19 has become a global epidemic since it first emerged in late 2019. Indonesia has made various efforts to prevent Covid-19, both through government policies and mass vaccination. Vaccine availability in mass vaccination policies is not sufficient because vaccines must be well accepted by the general public. One way to gain public trust is to make the impact of vaccination transparent by modeling its impact on the proportion of Covid-19 positive cases. In this study, we performed modeling using two main data sets. The first data is the number of people who received the first or second vaccine between July 1, 2021 and January 1, 2022. The second data is the positive rate (%) from July 15, 2021 to January 15, 2022. The results of this study show that increasing the proportion of the population vaccinated against Covid-19 with both 1st and 2nd doses can reduce the prevalence of Covid-19 cases in Indonesia. Moreover, increasing the proportion of second vaccinations further reduces the prevalence of Covid-19 cases compared to increasing the proportion of first vaccinations